Long-term outcomes of concomitant chemoradiotherapy with temozolomide for newly diagnosed glioblastoma patients: A single-center analysis - Roh, Tae Hoon (Medicine (Baltimore), 2017)
The present study analyzed outcomes of surgery followed by concomitant chemoradiotherapy (CCRT) with temozolomide (TMZ) in patients with newly diagnosed glioblastoma (GBM) at a single institution. Outcomes were retrospectively reviewed in 252 consecutive patients with newly diagnosed GBM who underwent surgery followed by CCRT with TMZ at the authors’ institution between 2005 and 2013. At initial operation, 126 (50.0%), 55 (21.8%), 45 (17.9%), and 26 (10.3%) patients underwent gross total resection (GTR), subtotal resection, partial resection (PR), and biopsy, respectively. Their median overall survival (OS) was 20.8 months (95% confidence interval [CI] 17.7–23.9 months) and their median progression-free survival was 12.7 months (95% CI 11.2–14.2 months). The O(6)-methylguanine-DNA methyltransferase (MGMT) promoter was methylated in 78 (34.1%) of the 229 patients assayed, and an isocitrate dehydrogenase 1 mutation was detected in 7 (6.6%) of the 106 patients analyzed. Univariate analyses showed that patient age, involvement of eloquent areas, involvement of the subventricular zone, presence of leptomeningeal seeding, Karnofsky Performance Status, extent of resection (EOR), MGMT promoter methylation, and presence of an oligodendroglioma component were prognostic of OS. Multivariate analysis showed that age, involvement of eloquent areas, presence of leptomeningeal seeding, EOR, and MGMT promoter methylation were significantly predictive of survival. OS in patients with GBM who undergo surgery followed by CCRT with TMZ is enhanced by complete resection. Other factors significantly prognostic of OS include that age, involvement of eloquent areas, presence of leptomeningeal seeding, and MGMT promoter methylation.